Use of ACE (Angiotensin-Converting Enzyme) Inhibitors and Risk of Lung Cancer: A Nationwide Nested Case-Control Study. Issue 1 (January 2021) - Kristensen, Kasper Bruun; Hicks, Blánaid; Azoulay, Laurent; Pottegård, Anton
Abstract : Background: Use of angiotensin-converting enzyme inhibitors (ACEIs)was associated with increased risk of lung cancer in a cohort study from the United Kingdom. We aimed to replicate these findings in a Danish population. Methods: We conducted a nested case-control study using data from 4 Danish national health and administrative registries. New users of ACEIs or angiotensin II receptor blockers in Denmark from January 1, 2000 were followed until December 31, 2015, incident lung cancer, death, or emigration. Each lung cancer case was matched with up to 20 controls on age, sex, duration of follow-up, and year of cohort entry using risk-set sampling. Conditional logistic regression was used to estimate odds ratios (ORs) for incident, histologically verified lung cancer with high use of ACEIs defined as a cumulative dose above 3650 defined daily doses. We examined different cumulative doses of ACEI (⩽1800, 1801–3650, >3650 defined daily doses), examined whether the association varied with lung cancer histology, and repeated the analyses using thiazides as active comparator. Results: We included 9652 lung cancer cases matched to 190 055 controls. High use of ACEIs was associated with lung cancer (adjusted OR, 1.33 [95% CI, 1.08–1.62]). Lower cumulative doses showed neutral associations (⩽1800 defined daily doses OR, 1.01 [95% CI, 0.94–1.09]; 1801–3650 defined daily doses OR, 1.03 [95% CI, 0.90–1.19]). CIs were wide and included the null when stratifying on histology. Using thiazides as active comparator yielded comparable results (OR, 1.34 [95% CI, 0.96–1.88]). Conclusions: Use of high cumulative ACEI doses was associated with modestly increased odds of lung cancer although use of lower doses showed neutral associations. The established benefits of ACEIs should be considered when interpreting these findings. Abstract : Supplemental Digital Content is available in the text.